COMMUNITY-BASED ECOTOURISM: A MODEL FOR SUSTAINABLE ECONOMIC DEVELOPMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Community-Based Ecotourism (CBET) is an innovative approach that integrates environmental conservation with local economic development. By engaging local communities in tourism management, CBET enhances economic opportunities while promoting sustainable practices. This paper explores the principles of CBET, its economic benefits, environmental impacts, and challenges in implementation. Case studies from different regions illustrate how CBET can contribute to sustainable development while preserving cultural and natural heritage.